Challenging pregnancy : a journey through the politics and science of healthcare in America - Grabman, Genevieve Marie, 1975- (University of Iowa Press, 2022)
"Challenging Pregnancy is about science and the politics of maternal healthcare in the US, where every woman must self-advocate for her desired outcome of her own pregnancy. I got pregnant with identical twins, whose circulatory systems were connected in a rare condition called twin-to-twin transfer syndrome (TTTS). Doctors couldn't "unfuse" the fetuses because one twin also had several other confounding problems: selective intrauterine growth restriction (SIUGR), a two-vessel umbilical cord, a marginal cord insertion, and, possibly, a parasitic triplet. Ultimately, national anti-abortion politics, and not medicine or my own choices, determined my pregnancy's outcome. At every decision, anti-abortion politics limited the care available to me, the doctors and hospitals willing to treat me, the tools doctors could use, and the words my doctors could say. Although I asked for aggressive treatment to save at least one baby, hospital ethics boards blocked all able doctors from helping me. My twins were born prematurely, and one almost died - twice - in the neonatal intensive care unit. The lessons from Challenging Pregnancy can guide women - and all voters - as they consider how healthcare policy affects each of us. We can determine where to push, where to demand change, what options we have, what choices we need, and how to maintain our sanity and good humor throughout"--